2022
DOI: 10.3389/fonc.2022.831112
|View full text |Cite
|
Sign up to set email alerts
|

Predicting the WHO/ISUP Grade of Clear Cell Renal Cell Carcinoma Through CT-Based Tumoral and Peritumoral Radiomics

Abstract: ObjectivesThis study aims to establish predictive logistic models for the World Health Organization/International Society of Urological Pathology (WHO/ISUP) grades of clear cell renal cell carcinoma (ccRCC) based on tumoral and peritumoral radiomics.MethodsA cohort of 370 patients with pathologically confirmed ccRCCs were included in this retrospective study between January 2014 and December 2020 according to the WHO/ISUP grading system. The volume of interests of triphasic computed tomography images were depi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 25 publications
0
2
0
Order By: Relevance
“…A study predicting the grading of renal clear cell carcinoma defined the peritumoral region as the area 2 mm, 5 mm, and 10 mm around the tumor, further dividing these regions into the peritumoral parenchyma and peritumoral fat. The results showed that the radiomic features of the peritumoral fat contained important predictive information [ 38 ]. However, our study found that the inclusion of peritumoral ROIs at 2 mm, 4 mm, or 6 mm did not significantly enhance the performance of the radiomics model beyond the use of only the intratumoral ROI.…”
Section: Discussionmentioning
confidence: 99%
“…A study predicting the grading of renal clear cell carcinoma defined the peritumoral region as the area 2 mm, 5 mm, and 10 mm around the tumor, further dividing these regions into the peritumoral parenchyma and peritumoral fat. The results showed that the radiomic features of the peritumoral fat contained important predictive information [ 38 ]. However, our study found that the inclusion of peritumoral ROIs at 2 mm, 4 mm, or 6 mm did not significantly enhance the performance of the radiomics model beyond the use of only the intratumoral ROI.…”
Section: Discussionmentioning
confidence: 99%
“…The use of radiomic features to characterize renal masses, predict prognosis and grade tumors has been a focus of research. CT-based radiomics have been identified as being predictive of WHO/ISUP grade [ 145 ]. FDG PET-CT has also been studied as a predictor of WHO/ISUP grade as well.…”
Section: Urological Malignanciesmentioning
confidence: 99%